Effectiveness of the Effort Program to Reduce Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) by the Health Office of Padang City - Monicha, Aprelia; Malau, Hasbullah (The Future of Education Journal, 2025)
This study aims to analyze the effectiveness of programs implemented by the Padang City Health Office to reduce maternal mortality (MMR) and infant mortality (IMR). The research is motivated by the fact that these indicators remain relatively high and serve as critical measures of public health and the success of regional development. The research uses a qualitative descriptive method, with data collected through in-depth interviews, field observations, and documentation. The results show that the maternal and infant mortality reduction program has been relatively effective, particularly in increasing antenatal care coverage, promoting maternal classes, and implementing community-based health innovations. However, challenges remain, such as uneven distribution of health personnel quality, limited inter-sectoral coordination, and low community participation in maternal and child health programs. The study concludes that program effectiveness can be improved through strengthening community awareness, cross-sectoral collaboration, and capacity building for health workers.